Дослідження можливості та перспектив використання каналу передачі з можливістю корекції помилок в області стеганографії - Сорокун, Антон Дмитрович (НТУ "ХПІ", 2017)
Розглядається такий спосіб організації захищеного спілкування двох суб’єктів від атак та ненавмисних змін, як стеганографія. Пропонується використовувати коди з можливістю виправлення помилок, описано механіку й принципи роботи з ними. В експериментальній частині тестується стеганографічна ємність кодів Ріда-Соломона і можливість включення додаткових біт інформації до стеганоповідомлення. Результатом дослідження є обґрунтування перспективи подальших досліджень застосування коригуючих кодів в області стеганографії.

The present disclosure is directed to several problems relating to the goal of steganography: to hide messages in such a way that no one other than the sender and the intended recipient knows about the existence of this message. It is proposed to use codes with the possibility of correction of errors, also described the mechanics and principles of working with them. In the experimental part, the steganographic capacity of the Reed-Solomon codes is tested. Research field include the possibility of adding additional bits of information to the secret message. The result of the study is to justify the prospect of further research on the use of corrective codes in the area of steganography.
Investigation of the possibility and prospects of using the transmission channel with the possibility of correction of errors in the field of steganography
Keywords: коригуючі коди; коди Ріда-Соломона; шифрування; мережі зв'язку; corrective codes; Reed-Solomon codes